Intraventricular Baclofen for Treatment of Severe Dystonia Associated with Glutaryl‐CoA Dehydrogenase Deficiency (GA1): Report of Two Cases. Issue 3 (5th January 2016) - Ghatan, Saadi; Kokoszka, Malgosia A.; Ranney, Anne M.; Strauss, Kevin A.
Abstract: Two individuals with intractable generalized dystonia secondary to glutaric aciduria type 1 (GA1) were treated with continuous intraventricular baclofen (IVB) infusion. On IVB of 220 μg/day, one 10‐year‐old girl had an 85% reduction in dystonia, from Barry‐Albright Dystonia Scale (BADS) score 30.7 to 4.5 (maximum score: 32) at 30 postoperative months. Her enteral dystonia medications were reduced >60%, and she discontinued medications for pain, anxiety, and depression. A second GA1 patient, age 23, experienced a more modest 18% reduction in dystonia (BADS decrease from 29.7 to 24.3) on IVB of 1, 665 μg/day at 14 postoperative months. He substantially reduced his enteral dystonia medications and reported meaningful pain relief. These cases demonstrate that IVB may be a palliative option in the intractable dystonia of GA1. Our provisional observations suggest that IVB may be more beneficial in younger GA1 patients.